Feasibility and Outcomes of Vessel-Sparing Surgery for Soft Tissue Sarcoma of the Thigh Adjacent to Femoral Vessels - Yang ZM; Qu H; Wang KY; Wu JD; Liu B; Jin LB; Huang X; Lin N; Tao HM; Ye ZM (Therapeutics and Clinical Risk Management)
Zheng-Ming Yang,1– 5,* Hao Qu,1– 5,* Ke-Yi Wang,1– 5 Jia-Dan Wu,1– 5 Bing Liu,1– 5 Li-Bin Jin,1– 5 Xin Huang,1– 5 Nong Lin,1– 5 Hui-Min Tao,1– 5 Zhao-Ming Ye1– 5 1Department of Orthopedics, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310000, People’s Republic of China; 2Orthopedics Research Institute, Zhejiang University, Hangzhou, Zhejiang, 310000, People’s Republic of China; 3Clinical Research Center of Motor System Disease of Zhejiang Province, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310000, People’s Republic of China; 4Zhejiang Key Laboratory of Motor System Disease Precision Research and Therapy, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310000, People’s Republic of China; 5State Key Laboratory of Transvascular Implantation Devices, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310009, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zheng-Ming Yang, Department of Orthopedics, The Second Affiliated Hospital of Zhejiang University School of Medicine, No. 1504 of Jiang Hon Road, BinJiang District, Hangzhou, Zhejiang, 310000, People’s Republic of China, Tel +8613758228633, Email 2200013@zju.edu.cnObjective: This study aims to investigate the feasibility and oncological outcomes of vessel-sparing surgery for soft tissue sarcomas located near the femoral vessels in the thigh. A comparison was made with cases where the tumor was not adjacent to the femoral vessels, focusing on recurrence rates, survival prognosis, and the viability of vessel-sparing surgical techniques.Methods: A retrospective analysis was conducted on 211 cases. After well-differentiated liposarcoma were excluded from further analysis, 148 cases involved tumors not adjacent to the femoral vessels, while 22 cases were located near the vessels. Postoperative functional outcomes, survival rates, and local recurrence were evaluated. Due to the imbalance in case numbers between the two groups, propensity score matching was applied at a 1:1 ratio, after which the two datasets were compared and analyzed.Results: By the last follow-up, 40 had experienced recurrence, 35 patients had died, 15 were surviving with tumors, and 161 were living tumor-free. No statistically significant differences were found between the survival and recurrence-free survival curves for cases with sarcomas adjacent to the femoral vessels compared to those with tumors located elsewhere, both before and after propensity score matching. Tumor grade and size were identified as key factors influencing survival and recurrence outcomes in soft tissue sarcoma of the thigh.Conclusion: For soft tissue sarcoma of the thigh located adjacent to femoral vessels, vessel-sparing surgery involving vascular sheath removal demonstrates favorable outcomes. Tumor size greater than 10 cm and high pathological grade were significant predictors of survival and recurrence risk.Keywords: femoral vessels, prognosis, soft tissue sarcoma, thigh, vascular resection